Chernigov Architecture in the Late 11th — First Third of the 12th Century and the Byzantine Architectural Practice - Trushnikova, Alexandra V. (Actual Problems of Theory and History of Art, 2019)
The Dormition cathedral, St. Boris and Gleb church, the Prophet Elijah church, the northwest chapel attached to the Savior Cathedral and the civil building (presumably the Prince’s palace) share the features unprecedented in Chernigov and Old Russian architecture. The new masonry technique and Romanesque elements were introduced by the new master-builders: either from the Byzantine Empire, or from the North of Italy. The point of view attributing the Chernigov churches only to the West European builders appears to be controversial. Rather than Lombardy and Emilia-Romagna, the Byzantine building practice could be the source of the following Chernigov innovations: the masonry technique without the concealed courses of brick, groin vaults, engaged columns, stained glass, ornaments of the mosaic floor decorations, painted plaster on the facades, chapels in the narthex and the upper gallery. The atrophied Greek-cross church type of the Elijah church and the attached churches in Chernigov architecture strengthen the links with the Byzantine tradition. The complex of Byzantine construction technique and decoration indicates connection of the builders that worked in Chernigov with the Byzantine capital architecture or with some region where Constantinople left quite a strong impact. The only undisputable Romanesque feature is the Lombard band, but its application to the cross-in-square church with narthex strikes as irregular in comparison with accuracy of the West European practice. This unique combination of Byzantine and Romanesque features requires further study of the building process and the donor activity in Chernigov in the late 11th — first third of the12th century.
Keywords: Old Russian architecture; Byzantine construction; Chernigov; technique without the concealed courses of brick; groin vault; engaged columns; the Lombard band; attached church